Structural and functional analysis of Hikeshi, a new nuclear transport receptor of Hsp70s. (1st March 2015) - Song, Jinsue; Kose, Shingo; Watanabe, Ai; Son, Se‐Young; Choi, Saehae; Hong, Hyerim; Yamashita, Eiki; Park, Il Yeong; Imamoto, Naoko; Lee, Soo Jae
<x xml:space="preserve">Abstract</x> Hikeshi is a nuclear transport receptor required for cell survival after stress. It mediates heat‐shock‐induced nuclear import of 70 kDa heat‐shock proteins (Hsp70s) through interactions with FG‐nucleoporins (FG‐Nups), which are proteins in nuclear pore complexes (NPCs). Here, the crystal structure of human Hikeshi is presented at 1.8 Å resolution. Hikeshi forms an asymmetric homodimer that is responsible for the interaction with Hsp70s. The asymmetry of Hikeshi arises from the distinct conformation of the C‐terminal domain (CTD) and the flexibility of the linker regions of each monomer. Structure‐guided mutational analyses showed that both the flexible linker region and the CTD are important for nuclear import of Hsp70. Pull‐down assays revealed that only full‐length Hsp70s can interact with Hikeshi. The N‐terminal domain (NTD) consists of a jelly‐roll/β‐sandwich fold structure which contains hydrophobic pockets involved in FG‐Nup recognition. A unique extended loop (E‐loop) in the NTD is likely to regulate the interactions of Hikeshi with FG‐Nups. The crystal structure of Hikeshi explains how Hikeshi participates in the regulation of nuclear import through the recognition of FG‐Nups and which part of Hikeshi affects its binding to Hsp70. This study is the first to yield structural insight into this highly unique import receptor.